2017
DOI: 10.5216/ree.v19.43587
|View full text |Cite
|
Sign up to set email alerts
|

Diretivas antecipadas de vontade: desafios legais e educacionais na visão de enfermeiros

Abstract: As Diretivas Antecipadas de Vontade (DAV) são um registro documental no qual o indivíduo descreve os procedimentos que gostaria ou não de ser submetido. Objetivou-se neste artigo discutir os desafios emergentes com o uso das DAV em termos éticos-legais e educacionais na visão de enfermeiros. Estudo qualitativo exploratório realizado mediante entrevistas semiestruturadas com 19 enfermeiros de Terapia Intensiva e Clínica Médica de um Hospital Universitário. A análise dos dados conduziu-se segundo a técnica de An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 8 publications
0
7
0
12
Order By: Relevance
“…These two associated conditions appear, according to Saioron I, Ramos FRS, Amadigi FR, Diaz OS (2017), presenting the culture of curative practice in academic formation as another factor and the view of death as a failure [18] in professional practice.…”
Section: Discussionmentioning
confidence: 99%
“…These two associated conditions appear, according to Saioron I, Ramos FRS, Amadigi FR, Diaz OS (2017), presenting the culture of curative practice in academic formation as another factor and the view of death as a failure [18] in professional practice.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in another university hospital in the South of Brazil, the professionals interviewed also highlighted the importance of respecting patients' autonomy, but said they felt insecure in following ADs because there is no legislation to safeguard them 15 . Another study revealed that most respondents (nurses, doctors and pharmacists) declared they would respect the will expressed in ADs if they were legally guaranteed 21 .…”
Section: Researchmentioning
confidence: 99%
“…In this sense, the lack of legal support and the deficient approach to terminality in medical schools -traditionally focused on techniques and cure -generate insecurity and limit the role of AD, treated as mere additional information, without much relevance to direct therapeutic behaviors 15 . Although they recognize the importance of knowing the patient's will, professionals feel the need to protect themselves from possible judicial problems.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Este documento não é obrigatório e pode ser feito apenas por maiores de idade em plena consciência de seus atos. Dentre os últimos 20 anos, vários países buscam discutir acerca deste procedimento objetivando um consenso dentro da ética terapêutica(SAIORON;.Dentro do aspecto brasileiro, neste documento somente fica inviável a autorização para a eutanásia, prática médica que permite a desligada de aparelhos de pacientes em estados terminais e inconscientes. Após a resolução deste processo no Brasil, observouse o crescimento de 700% pela sua procura, levando a um conhecimento midiático da situação(ALENCASTRO, 2012).Segundo Nunes e Anjos (2014) uma parte da classe médica brasileira enxerga a DAV como um instrumento tecnológico de suma importância, porém, os desejos do paciente precisam estar dentro dos padrões da bioética, do contrário, se torna inviável para a equipe a realização de sua DAV, conforme Mabtum e Marchetto(2015).…”
unclassified